2011
DOI: 10.1371/journal.pone.0016239
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic Myocardial Damage Is Mediated by Proinflammatory Cytokine: Macrophage Migration Inhibitory Factor

Abstract: BackgroundDiabetes has been regarded as an inflammatory condition which is associated with left ventricular diastolic dysfunction (LVDD). The purpose of this study was to examine the expression levels of macrophage migration inhibitory factor (MIF) and G protein-coupled receptor kinase 2 (GRK2) in patients with early diabetic cardiomyopathy, and to investigate the mechanisms involved in MIF expression and GRK2 activation.Methods83 patients in the age range of 30-64 years with type 2 diabetes and 30 matched hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 32 publications
1
46
1
1
Order By: Relevance
“…Interestingly, we detected that heart increased its endogenous production of MIF. While this autocrine/endocrine function has been previously illustrated in sepsis [14] and ischemia/reperfusion injury [18], the overall cardiac effects of MIF are challenging as both protective and deleterious consequences have been reported [18], [30][32].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we detected that heart increased its endogenous production of MIF. While this autocrine/endocrine function has been previously illustrated in sepsis [14] and ischemia/reperfusion injury [18], the overall cardiac effects of MIF are challenging as both protective and deleterious consequences have been reported [18], [30][32].…”
Section: Discussionmentioning
confidence: 93%
“…Another study also showed that hyperglycemic myocardial damage was mediated by proinflammatory cytokines (Yu et al, 2011). Furthermore, exposure to HG was found to enhance MMP-1 expression of macrophages in response to inflammatory stimuli (Maldonado et al, 2004).…”
Section: +mentioning
confidence: 90%
“…In experimental STZ‐induced T1D models of diabetic cardiomyopathy, NF‐κB activation was shown to be correlated with the increased release of IL‐1β and TNF‐α 113, 114, 115. Moreover, elevated levels of these two pro‐inflammatory cytokines have been found in the circulation and hearts of patients with T2D 116. In fact, several studies report a strong correlation between the characteristic hallmarks of diabetic cardiomyopathy and the levels NF‐κB and cytokines 113.…”
Section: Diabetic Cardiomyopathy Antioxidant Defences and Immunothermentioning
confidence: 99%
“…This, in turn, drives the production of extracellular matrix (ECM) proteins in the heart, including collagen, fibronectin and proteoglycans, leading to fibrosis, LV remodelling and stiffness, and reduced relaxation of the heart 108, 117. Moreover, a clinical study showed a correlation between macrophage inhibitory factor and the development of diastolic dysfunction in diabetic patients 116. This is of interest as one of the glucagon‐like peptide 1 (GLP‐1) agonists, exendin‐4, a drug class primarily employed in the clinic due to its inherent ability to lower blood glucose, was shown to attenuate adverse cardiac remodelling in diabetic mice, specifically by reducing inflammation, independent of its known glucose‐lowering actions 118…”
Section: Diabetic Cardiomyopathy Antioxidant Defences and Immunothermentioning
confidence: 99%